Molecular signaling and regulation in glial sells: a key to remyelination and functional repair - Jeserich, Gunnar (Springer Berlin Heidelberg, 1997)
An excellent survey of the most recent advances in the area of cellular and molecular biology of glial cells and their involvement in remyelination and functional repair in the CNS. A major part of this book deals with signaling paths within and among neural cells. Glial cells (astrocytes, oligodentrocytes, microglial cells) themselves release substantial amounts of cytokines, growth factors and other signaling molecules, which play an important role during injury and regeneration. Another signaling route between neurons and glial cells follows ion channels and neurotransmitter receptors. In addition to animal models, human oligodentrocytes in cell culture and in the human MS brain are characterized with respect to their immunocytochemistry and function
Lizenzpflichtig
Keywords: Konferenzschrift; Remyelinisierung; Gliazelle; Zentralnervensystem; Regulation; Signaltransduktion